Differences in magnetic particle uptake by CNS neuroglial subclasses: implications for neural tissue engineering. (June 2013) - Jenkins, Stuart I; Pickard, Mark R; Furness, David N; Yiu, Humphrey HP; Chari, Divya M
Aim: To analyze magnetic particle uptake and intracellular processing by the four main non-neuronal subclasses of the CNS: oligodendrocyte precursor cells; oligodendrocytes; astrocytes; and microglia.Materials & methods: Magnetic particle uptake and processing were studied in rat oligodendrocyte precursor cells and oligodendrocytes using fluorescence and transmission electron microscopy, and the results collated with previous data from rat microglia and astrocyte studies. All cells were derived from primary mixed glial cultures.Results: Significant intercellular differences were observed between glial subtypes: microglia demonstrate the most rapid/extensive particle uptake, followed by astrocytes, with oligodendrocyte precursor cells and oligodendrocytes showing significantly lower uptake. Ultrastructural analyses suggest that magnetic particles are extensively degraded in microglia, but relatively stable in other cells.Conclusion: Intercellular differences in particle uptake and handling exist between the major neuroglial subtypes. This has important implications for the utility of the magnetic particle platform for neurobiological applications including genetic modification, transplant cell labeling and biomolecule delivery to mixed CNS cell populations. Original submitted 23 March 2012; Revised submitted 24 July 2012; Published online 22 November 2012